INVESTIGATION ON ANTIDIARRHOEAL ACTIVITY OF ARISTOLOCHIA INDICA LINN. ROOT EXTRACTS IN MICE - Dharmalingam, Senthil Rajan; Madhappan, Rajkumar; Ramamurthy, Srinivasan; Chidambaram, Kumarappan; Srikantha, Meka Venkata; Shanmugham, Suresh; KL, Senthil Kumar (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The present study aimed at investigating the effect of ethanolic extract (EtAI), and aqueous extract (AqAI) of Aristolochia indica Linn roots on castor oil-induced diarrhoea and study on small intestinal transit. Phytochemical analysis of extracts was performed as per standard procedure. Materials and Methods: The oral toxicity study using Swiss albino mice was performed in accordance with OECD guidelines. The EtAI and AqAI extracts of Aristolochia indica Linn were studied for antidiarrhoeal property using castor oil-induced diarrhoeal model and charcoal-induced gastrointestinal motility test in Swiss albino mice. Results: Among the tested doses of 200 and 400 mg/kg body weight, the extracts reduced the frequency and severity of diarrhoea in test animals throughout the study period. At the same doses, the extract delayed the intestinal transit of charcoal meal in test animals as compared to the control and the results were statistically significant. Conclusion: Experimental findings showed that ethanol extract of Aristolochia indica Linn root possess significant antidiarrheal activity and may be a potent source of anti-diarrhoeal drug in future.